Effectiveness of Intravenous Subanesthetic Dose of Ketamine on the Subarachnoid Block to Attenuate Inflammation Response in Transurethral Resection of the Prostate Surgeries - Tjokorda Gde Agung Senapathi (Journal of Global Pharma Technology, 2019)
Background: Perioperative anesthesia and surgery can induce a stress response in the body. Regional anesthesia with local anesthetic drugs in the transurethral Resection of the Prostate (TUR-P), has been proven to minimize inflammation. Patients and Methods: Forty-eight patients of ASA I-II, scheduled for TUR-P with spinal subarachnoid anesthesia were randomly divided into two groups, group A with ketamine and group B without ketamine. The blood level of interleukin (IL)-10, IL-8, C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), and IL-10/IL-8 ratio were measured in both groups at 1 hour before operation, also at 1 and 24 hours after operation. Results: Blood level of IL-10 (p<0.001) and IL-10/IL-8 Ratio (p<0.05) were significantly different with higher values on group A. Other parameters were not found to be different. Conclusion: Subanesthetic dose of ketamine on spinal subarachnoid anesthesia technique done for TUR-P operation was found able to control inflammation and prevent the deterioration of immune system perioperatively.Keywords: IL-10, IL-8, CRP, NLR, Benign prostatic hyperplasia.